The Influence of Effort-Reward Imbalance, Organizational Support, and Work Procrastination on Counterproductive Behavior of Health Workers - Marissa; Nining Handayani; Yani Restiani Widjaja (Technium Business and Management, 2026)
Counterproductive Work Behavior (CWB) can hinder the achievement of organizational goals. In the healthcare sector, particularly hospitals, CWB by healthcare workers can reduce the quality of patient care and create a non-conducive work environment. This study aims to determine the effect of Effort-Reward Imbalance (ERI), Perceived Organizational Support (POS), and Workplace Procrastination (WP) on CWB of healthcare workers at Ciawi Regional General Hospital (RSUD). The method used in this study was quantitative confirmatory. research using probabilistic and stratified sampling techniques random sampling. The data analysis technique was carried out using the Partial Sample method. Least Squares – Structural Equation Modeling (PLS-SEM). The analysis results indicate that ERI, POS, and CWB are able to explain 58.5% of the variation in CWB among healthcare workers at Ciawi Regional Hospital. This value is categorized as adequate, so this model is suitable for use to explain the phenomenon of counterproductive behavior in healthcare organizations. The results of the study indicate that ERI and WP have a positive and significant influence on healthcare workers at Ciawi Regional Hospital, while POS has a negative and significant influence on CWB. The simultaneous equation of the SEM model, namely CWB = 0.330·ERI − 0.320·POS + 0.335·WP, proves that the higher the ERI and WP, the higher the tendency of healthcare workers to engage in CWB, while the higher the POS, the lower the tendency of CWB. A comprehensive managerial strategy based on these research indicators is expected to be the basis for creating a productive work environment and maintaining service quality at Ciawi Regional Hospital.